Assessing the Anti-Colitis Properties of Aqueous and Hydroalcoholic Extracts of Pinus eldarica in Rats with Acetic Acid-Induced Colitis - Mohsen Minaiyan*; Zahra Dastanian; Behzad Zolfaghari; Ardeshir Talebi (Iranian Society of Pharmacognosy, 2024)
Background and objectives: Ulcerative colitis is a challenging inflammatory bowel disease that requires new treatments. Pinus eldarica can be a suitable candidate for this disease due to its anti-inflammatory, anti-ulcerative and antioxidant properties. Methods: Pinus eladarica aqueous and hydroalcoholic extracts of barks were standardized according to the total phenols, flavonoids and proanthocyanidin contents. Three doses (100, 200, and 400 mg/kg, p.o.) of both extracts were separately administered to rats with acetic acid-induced colitis for a period of five days. Reference groups received dexamethasone (1 mg/kg, i.p.) or mesalazine (150 mg/kg, p.o.) while control groups were treated with normal saline. Results: Both extracts reduced the macroscopic parameters of colitis (weight of colon, ulcer area, ulcer severity and ulcer index) significantly compared with control groups, especially in lower doses (100, 200 mg/kg). Similarly, the extracts improved the microscopic parameters (severity and extent of inflammation, leukocyte infiltration, crypt damage, and total colitis score) except for the dose of 400 mg, which was not effective. The decrease in myeloperoxidase activity and malondeladehyde values ​​was also significant for both extracts at all doses. Conclusion: Pinus eldarica bark extracts are effective in treating and reducing the damage caused by colitis, although it is necessary to adjust the effective dosage. Lower doses of extracts, especially hydroalcoholic one showed better therapeutic effects. Further studies are necessary to identify effective compounds, particularly in the hydroalcoholic extract, for producing an herbal drug for the clinical setting.